2014
DOI: 10.1155/2014/947560
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Action of Synthetic Stigmasterol Derivatives on Herpes Simplex Virus Replication in Nervous CellsIn Vitro

Abstract: Polyfunctionalized stigmasterol derivatives, (22S,23S)-22,23-dihydroxystigmast-4-en-3-one (compound 1) and (22S,23S)-3β-bromo-5α,22,23-trihydroxystigmastan-6-one (compound 2), inhibit herpes simplex virus type 1 (HSV-1) replication and spreading in human epithelial cells derived from ocular tissues. Both compounds reduce the incidence and severity of lesions in a murine model of herpetic stromal keratitis when administered in different treatment modalities. Since encephalitis caused by HSV-1 is another immunop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…In a previous study, Saikogenin G was demonstrated to exhibit an anti-inflammatory activity against carrageenan produced plantar edema in rats [ 16 ]. Stigmasterol has exhibited anti-inflammatory and immunomodulatory effects through the downregulation of proinflammatory cytokines; moreover, it has been shown to inhibit herpes simplex virus replication in nervous cells in vitro [ 17 , 18 ]. Devi and Periyanayagam found that Salvigenin derived from Plectranthus amboinicus exerted anti-inflammatory effects through human red blood cell (HRBC) membrane stabilization [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, Saikogenin G was demonstrated to exhibit an anti-inflammatory activity against carrageenan produced plantar edema in rats [ 16 ]. Stigmasterol has exhibited anti-inflammatory and immunomodulatory effects through the downregulation of proinflammatory cytokines; moreover, it has been shown to inhibit herpes simplex virus replication in nervous cells in vitro [ 17 , 18 ]. Devi and Periyanayagam found that Salvigenin derived from Plectranthus amboinicus exerted anti-inflammatory effects through human red blood cell (HRBC) membrane stabilization [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Investigation of anti‐herpes activity of the compounds in vitro was carried out in accordance with the internationally accepted cytopathic effect (CPE) inhibition assay (De Clercq et al., ; Fedorov et al., ; Petrera, Níttolo, & Alché, ) . In 96‐well plastic plates (Linbro, Flow Laboratories, UK) with the generated cell monolayers, the twofold serial dilutions of the compounds were prepared in the support medium (Eagle medium and medium 199, 1: 1).…”
Section: Methodsmentioning
confidence: 99%
“…Presently, eight different human herpes viruses have been recognized out of which herpes simplex (HSV) is omnipresent. Herpes infection is characterized by their aptitude to cause lifelong infections [84].…”
Section: Antiherpetic Activitiesmentioning
confidence: 99%
“…It was suggested that these two compounds suppressed the replication of HSV-1 in nervous cells and its proliferation in human epithelial cells. Cytokine levels were determined after treatment with these compounds which reflected decreased levels of IL-6 and IFN-α in HSV-1 infected-Neuro-2a cells that demonstrated anti-inflammatory activities within them [84]. Reports by Michelini et al [54] suggested that this compound reduced cytokine production in LPS activated macrophages and enhanced pro-inflammatory cytokine production in HSV-1 infected epithelial cells of mice cells.…”
Section: Anti-inflammatory Activitiesmentioning
confidence: 99%